Nutritional and biochemical insights into multiple pressure ulcer management: a case report - Hokynková, Alica; Paulová, Hana; Šín, Petr; Nováková, Marie; Babula, Petr; Pokorná, Andrea (Frontiers in Nutrition, 2025)
This case report presents a unique study focused on relationship between nutritional parameters, C-reactive protein (CRP), and the marker of oxidative stress 8-hydroxy-2′-deoxyguanosine (8-OHdG), in 61-year-old male paraplegic patient with multiple pressure ulcers. A multidisciplinary approach was essential for the timing of the successful reconstruction process. The patient had a history of paraplegia since 1999 due to a skiing accident with fractures of thoracic vertebrae (Th6–Th9), requiring spinal surgery. His medical background includes acute pancreatitis with biliary tract revisions, partial pancreatic resection, acute respiratory failure with tracheostomy, renal failure treated with hemodialysis, bronchopneumonia, pseudomembranous colitis, and hyperuricemia. The patient also underwent multiple surgical interventions, including treatment for ulnar nerve paresis, cholecystectomy, and multiple pressure ulcer reconstructions. The study describes the relationship between selected biochemical parameters and overall clinical status in a paraplegic patient with three deep pressure ulcers located in the left-sided ischial, trochanteric, and sacral regions during their multistage surgical therapy. The reconstructive procedure and collection of biological samples for determination of selected biochemical parameters were performed according to the same schedule: debridement of pressure ulcers at the beginning of the particular hospitalization and on the day of surgical reconstruction. The patient’s severe condition was accompanied by decreased levels of both 8-OHdG and selected nutritional parameters (albumin, prealbumin, and total protein) and increased CRP levels at the beginning of the treatment process. The evaluation of the dynamics of the measured parameters during the gradual improvement of the patient’s condition and the multistage reconstruction of pressure ulcers in six hospitalizations over a period of 17 months was continued resulting in the healing of all pressure ulcers. This case highlights the crucial importance of investigating selected biochemical parameters, with emphasis on 8-OHdG, and nutritional parameters, for the timing of surgical strategy and comprehensive therapy in patients with multiple pressure ulcers and severe, complex medical histories.